Analisis Produksi Usaha Amplang Di Desa Tabanio Kabupaten Tanah Laut - Audina, Fitria; Nuryadin, Muhammad Rusmin (PPJP ULM, 2019)
This study was conducted to (1) analyze what factors influence the amount of production inthe Amplang business in Tabanio Village, Tanah Laut Regency; (2) explore the scale of theamplang production business in Tabanio village, Tanah Laut Regency; and (3) analyzing thelevel of efficiency of the amplang production business in Tabanio Village, Tanah Laut Regency.By using the Cobb-Douglas model.This study indicates that simultaneous production factors (primary raw material 1, mainraw material 2, supporting raw materials 1, supporting raw materials two, and labor wageshave no significant effect.The results of the envelope production scale in Tabanio Village, Tanah Laut Regency,decrease return ti scale with a production elasticity of 0,936. While input use efficiency is theprimary raw material, two and supporting raw material, one is still inefficient. In contrast, rawmaterial input central 1, keeping raw material 2 and labor wages, is inadequate.